Abordagem sobre os possíveis mecanismos de ação das soluções homeopáticas ultradiluídas - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Homeopathy is a medical science developed by Samuel Hahnemann, based on the law of themes and the vitalist concept. The four basic pillars of homeopathy are the law of similarity, experimentation on the healthy man, the single remedy and the minimum doses. It is known of its total effectiveness in clinical observation. However, the major challenge of current science is to explain in a scientific way the phenomenon of homeopathic high-dilutions. There are currently two main lines of research that attempt to explain the possible mechanisms of action of homeopathic dilutions or minimum doses: molecular theory and non-molecular theory. The objective of the present work is to carry out a review addressing the possible mechanisms of action of homeopathic drugs involving molecular theories based on physical-chemical and non-molecular models based on biological concepts in order to explain the phenomenon of ultradiluted solutions.
Approach to the possible mechanisms of action of ultra-diluted homeopathic solutions
Keywords: Farmácia; Homeopatia; mecanismo de ação; Soluções ultradiluídas; Homeopathy; Mechanism of action; high-dilutions; Pharmaceutical Sciences; CNPQ::CIENCIAS DA SAUDE